Benchmarking for research-related competencies: a curricular mapping approach at medical faculties in Germany - Lammerding-Köppel, Maria; Narciß, Elisabeth (Medical teacher, 2018)
Objectives: Internationally, scientific and research-related competencies need to be sufficiently targeted as core outcomes in many undergraduate medical curricula. Since 2015, standards have been recommended for Germany in the National Competency-based Learning Objective Catalogue in Medicine (NKLM). The aim of this study is to develop a multi-center mapping approach for curricular benchmarking against national standards and against other medical faculties.Method: A total of 277 faculty members from four German medical faculties have mapped the local curriculum against the scientific and research-related NKLM objectives, using consented procedures, metrics, and tools. The amount of mapping citations of each objective is used as indicator for its weighting in the local curriculum. Achieved competency levels after five-year education are compared.Results: All four programs fulfill the NKLM standards, with each emphasizing different sub-competencies explicitly in writing (Scholar: 17-41% of all courses; Medical Scientific Skills: 14-37% of all courses). Faculties show major or full agreement in objective weighting: Scholar 44%, scientific skills 79%. The given NKLM competency level is met or even outperformed in 78-100% of the courses.Conclusions: The multi-center mapping approach provides an informative dataset allowing curricular diagnosis by external benchmarking and guidance for optimization of local curricula.